Rural and Ethnic Disparities in Out-of-Hospital Care and Transport Pathways After Road Traffic Trauma in New Zealand. - Lilley, Rebbecca; Davie, Gabrielle; Dicker, Bridget; Reid, Papaarangi; Ameratunga, Shanthi; Branas, Charles; Campbell, Nicola; Civil, Ian; Kool, Bridget (California Digital Library (CDL), 2024)
INTRODUCTION: The out-of-hospital emergency medical service (EMS) care responses and the transport pathways to hospital play a vital role in patient survival following injury and are the first component of a well-functioning, optimised system of trauma care. Despite longstanding challenges in delivering equitable healthcare services in the health system of Aotearoa-New Zealand (NZ), little is known about inequities in EMS-delivered care and transport pathways to hospital-level care. METHODS: This population-level cohort study on out-of-hospital care, based on national EMS data, included trauma patients <85 years in age who were injured in a road traffic crash (RTC). In this study we examined the combined relationship between ethnicity and geographical location of injury in EMS out-of-hospital care and transport pathways following RTCs in Aotearoa-NZ. Analyses were stratified by geographical location of injury (rural and urban) and combined ethnicity-geographical location (rural Māori, rural non-Māori, urban Māori, and urban non-Māori). RESULTS: In a two-year period, there were 746 eligible patients; of these, 692 were transported to hospital. Indigenous Māori comprised 28% (196) of vehicle occupants attended by EMS, while 47% (324) of patients' injuries occurred in a rural location. The EMS transport pathways to hospital for rural patients were slower to reach first hospital (total in slowest tertile of time 44% vs 7%, P ≥ 0.001) and longer to reach definitive care (direct transport, 77% vs 87%, P = 0.001) compared to urban patients. Māori patients injured in a rural location were comparatively less likely than rural non-Māori to be triaged to priority transport pathways (fastest dispatch triage, 92% vs 97%, respectively, P = 0.05); slower to reach first hospital (total in slowest tertile of time, 55% vs 41%, P = 0.02); and had less access to specialist trauma care (reached tertiary trauma hospital, 51% vs 73%, P = 0.02). CONCLUSION: Among RTC patients attended and transported by EMS in NZ, there was variability in out-of-hospital EMS transport pathways through to specialist trauma care, strongly patterned by location of incident and ethnicity. These findings, mirroring other health disparities for Māori, provide an equity-focused evidence base to guide clinical and policy decision makers to optimize the delivery of EMS care and reduce disparities associated with out-of-hospital EMS care.
Keywords: Humans; New Zealand; Accidents, Traffic; Emergency Medical Services; Healthcare Disparities; Male; Female; Adult; Middle Aged; Rural Population; Wounds and Injuries; Transportation of Patients; Aged; Native Hawaiian or Other Pacific Islander; Adolescent; Health Services Accessibility; Ethnicity; Urban Population; Cohort Studies